SPIRITUAL NEUROSCIENCE IN PSYCHOLOGICAL PROBLEMS OF OLDER PEOPLE - MIERRINA; SITI KHORRIYATUL KHOTIMAH; DITA KURNIA SARI (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
This research is intended to determine the relationship between spiritual neuroscience and the psychological problems of elderly people. The samples in this study were members of the Majlis Ta'lim and Posyandu for the Elderly, pre-elderly and the elderly with an age range of 55-75 years. Taken using a Purposive Random Sampling technique, a total of 35 mothers were members of the Majlis Ta'lim and 37 mothers at the Elderly Posyandu. This research is research with a quantitative approach, to test correlations or relationships. The aim was to see the relationship between spiritual neuroscience and the psychological problems of elderly people, which was carried out in two communities, namely Majlis Ta'lim and Posyandu for the Elderly. Based on the hypothesis proposed, this research uses statistical analysis techniques of the product moment correlation test. The research results show that there is a correlation coefficient (r) of 1 and -0.654. This figure shows that there is a correlation between Elderly Problems and Spiritual Neuroscience (above 0.5), while the '-' sign indicates that the weaker the elderly's spiritual neuroscience, the higher the psychological problems experienced by the elderly, and vice versa, the stronger the elderly's spiritual neuroscience, the fewer  psychological problems experienced by the elderly.